2018
DOI: 10.1016/j.jpolmod.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Real and financial shocks, exchange rate regimes and the probability of a currency crisis

Abstract: We analyze the relationships among shocks, exchange rate regimes, and capital controls in relation to the probabilities of currency crises. Based on the theoretical model by Nakatani (2016Nakatani ( , 2017a, we use panel data on 34 developing countries and apply a probit estimation. We find that both productivity shocks and country risk premium shocks trigger currency crises, whereas productivity shocks are important for severe currency crises. We also find that the effects of these shocks on the probability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
0
14
0
4
Order By: Relevance
“…Current Deficit Balance Constraint: For an economy, being unable to balance the current deficit with financial account causes currency crises in the country [65]. The currency crises might not only trigger other financial and public crises, but also might cause cumulative 5-7% shrinkage in the GDPs of the economies [66] (p. 79).…”
Section: Constraintsmentioning
confidence: 99%
“…Current Deficit Balance Constraint: For an economy, being unable to balance the current deficit with financial account causes currency crises in the country [65]. The currency crises might not only trigger other financial and public crises, but also might cause cumulative 5-7% shrinkage in the GDPs of the economies [66] (p. 79).…”
Section: Constraintsmentioning
confidence: 99%
“…Liu, Wei, Shi, and Chang (2018) empirically finds highrisk economies are more likely to choose a fixed regime with a low level of composite and political risk in the government. Nakatani (2018) shows that capital controls mitigate the effects of productivity shocks in pegged regimes. Some literatures believe the floating exchange rate regime is a good choice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In line with the results, the likelihood of currency crises increased when credit to the private sector increased, while it decreased when GDP growth rates were high and also when the level of net foreign assets was high. Nakatani (2018) examined the likelihood of a currency crisis on a sample of 34 developing countries using the probit method. Practical results demonstrated that productivity shocks and risk premium shocks were important predictors of currency crises.…”
Section: Literature Reviewmentioning
confidence: 99%